Composite of Elastin-Based Matrix and Electrospun Poly(L-Lactic Acid) Fibers: A Potential Smart Drug Delivery System - Bandiera, Antonella; Passamonti, Sabina; Dolci, Luisa Stella; Focarete, Maria Letizia (Frontiers in Bioengineering and Biotechnology, 2018)
Stimuli-responsive hydrogel matrices are inspiring manifold applications in controlled delivery of bioactive compounds. Elastin-derived polypeptides form hydrogel matrices that may release bioactive moieties as a function of local increase of active elastases, as it would occur in several processes like inflammation. In view of the development of a patch for healing wounds, recombinant elastin-based polypeptides were combined with a proteolysis-resistant scaffold, made of electrospun poly-L-lactic acid (PLLA) fibers. The results of this study demonstrated the compatibility of these two components. An efficient procedure to obtain a composite material retaining the main features of each component was established. The release of the elastin moiety was monitored by means of a simple protocol. Our data showed that electrospun poly-L-lactic acid (PLLA) can form a composite with fusion proteins bound to elastin-derived polypeptides. Therefore, our approach allows designing a therapeutic agent delivery platform to realize devices capable of responding and interacting with biological systems at the molecular level.